Application of thermography in the identification of infiltractions and pipes for conducting cold water and hot water embedded in masonry (Research, Society and Development, 2021)
The methodology of infrared thermography (IRT) has been applied to the analysis of civil constructions to detect pathologies and anomalies, allowing human eye to "read" the temperature of objects. Given the importance of carrying out the identification of pipes embedded in masonry, in cases when hydraulic and sanitary projects does not exist anymore, the objective of the present work was to apply the IRT methodology to: identify non perceptible infiltrations and to investigate its use for inlaid pipe´s detection of cold and hot water. Regarding the identification of infiltrations, the results confirmed the adequacy of the methodology for this purpose, including for the detection of non-perceptible infiltrations. However, for the identification of hydraulic pipes embedded in the walls, the methodology presented the limitation when being executed in a ceramic wall, which blocks the capture of the wall temperature. In the investigation of simple cladding walls, the IRT was not efficient to identify cold water pipes, however, it indicates the potential of thermography for the detection of hot water pipes, since there is high temperature gradient between the pipe and the wall.